2014
DOI: 10.1371/journal.pone.0093362
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel Like Factor 4 Promoter Undergoes Active Demethylation during Monocyte/Macrophage Differentiation

Abstract: The role of different lineage specific transcription factors in directing hematopoietic cell fate towards myeloid lineage is well established but the status of epigenetic modifications has not been defined during this important developmental process. We used non proliferating, PU.1 inducible myeloid progenitor cells and differentiating bone marrow derived macrophages to study the PU.1 dependent KLF4 transcriptional regulation and its promoter demethylation during monocyte/macrophage differentiation. Expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 45 publications
0
37
0
Order By: Relevance
“…These observations suggest that AID is involved in the epigenetic changes that establish the EMT transcriptional program. Karpurapu et al reached a similar conclusion, finding that decreased AID expression blocked myeloid progenitor cell maturation, as judged by their morphology, and that AID is essential for the demethylation of Klf4, a gene involved in inflammatory monocyte differentiation [39]. Furthermore, Ratnu et al, investigating primary cultures of post-mitotic cortical neurons, reported that AID is involved in the demethylation of Bdnf, an activity-dependent gene necessary for neuronal survival [40].…”
Section: Other Systemsmentioning
confidence: 85%
See 2 more Smart Citations
“…These observations suggest that AID is involved in the epigenetic changes that establish the EMT transcriptional program. Karpurapu et al reached a similar conclusion, finding that decreased AID expression blocked myeloid progenitor cell maturation, as judged by their morphology, and that AID is essential for the demethylation of Klf4, a gene involved in inflammatory monocyte differentiation [39]. Furthermore, Ratnu et al, investigating primary cultures of post-mitotic cortical neurons, reported that AID is involved in the demethylation of Bdnf, an activity-dependent gene necessary for neuronal survival [40].…”
Section: Other Systemsmentioning
confidence: 85%
“…Evidence for a role of AID in genome-wide demethylation is also limited, either because the effect is subtle, as in the PGC study [29], or because the introduction of artificial constructs might not be physiologically relevant, as in the zebrafish study [25] or the GAL4/UAS system [24]. However, AID knockdown led to the loss of neurons in zebrafish [25] and clear cellular and molecular phenotypes in three independent systems [38][39][40], suggesting that AID may be involved in key gene-specific demethylation events linked to differentiation of non-lymphoid cells. These findings beg the question: is AID-dependent demethylation also observed in B cells?…”
Section: Other Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA methylation is thought to provide a chemically stable mark that serves to initiate and reinforce these cell fate decisions. 2 Large-scale methylation studies of specific lineage pathways have been performed on differentiating erythroid, 3,4 T lymphocyte, 5,6 B lymphocyte, 7 and myeloid 4 cells. These important developmental studies reveal insights into the regulation of cell fate decisions but also serve as a potential source of biomarkers that help characterize different immune compartments during the immune response.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, dynamic changes were also observed in the expression of the TET2, DNMT1, DNMT3A and DNMT3B genes coupled with temporal locus-specific demethylation of SRC, AHRR, CYP1B1 and PPARG, providing possible mechanisms accounting for the loss in DNA methylation (Zhang, Ulm, 2014). In addition, recent findings showed that Activation Induced Cytidine Deaminase (AICDA) mediated active demethylation of the KLF4 promoter, which is necessary for PU.1-mediated transcriptional regulation during monocyte/macrophage differentiation (Karpurapu et al, 2014).…”
Section: Epigenetic Dynamics In the Innate Immune Systemmentioning
confidence: 99%